2008
DOI: 10.1002/adfm.200701431
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of lattice ordering in thin film opal‐based photonic crystals

Abstract: This work is devoted to the quantitative evaluation of the lattice ordering of opal films. Assembling colloidal crystals in a moving meniscus under random noise agitation produced opal films with generically the same lattice but different disorders. The lattice ordering is quantified by the magnitudes of harmonics in the Fourier transforms of (i) the scanning electron microscopy images to address the in‐plane lattice ordering and (ii) rotation diagrams of the optical transmission to address the regularity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Previous work has identified the influence of deposition time at a given voltage, for opal template formation. 32 Additional deposition approaches involving white noise during dip-coating methods, 13,32,33 spin-coating techniques 34 or other assembly approaches to minimize crack formation have been reasonably successful. 33,[35][36][37][38] We have found that an increase in voltage to 2.5 or 3.0 V does affect ordering on a SS substrate (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has identified the influence of deposition time at a given voltage, for opal template formation. 32 Additional deposition approaches involving white noise during dip-coating methods, 13,32,33 spin-coating techniques 34 or other assembly approaches to minimize crack formation have been reasonably successful. 33,[35][36][37][38] We have found that an increase in voltage to 2.5 or 3.0 V does affect ordering on a SS substrate (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments we used an opal fi lm templates with improved crystallinity prepared in a vertically moving meniscus under white noise agitation of suspension. [ 81 ] Opal lattice is commonly described as a face centered cubic (fcc) package of touching spheres. In reality, the opal lattice is slightly stretched along the direction of pulling it out of suspension during crystallization.…”
Section: Opal On Metal -Towards Cavity Resonancementioning
confidence: 99%
“…The crystals formed with convective assembly show a tendency towards FCC stacking, which has inspired detailed studies of the assembly process [92][93][94][95] . Moreover, the need to prepare perfect defect-free crystals for photonic applications, resulted in the identification of different defect structures and their causes [42,96,97] , and has even led to control over defect incorporation [98][99][100][101][102] . The thickness and uniformity of the colloidal crystals can be controlled by several experimental factors during the convective assembly process.…”
Section: Convective Assemblymentioning
confidence: 99%
“…At ω = 0° the horizontal peak is located at q = 0.0111 nm -1 giving a lattice spacing of 566 nm. From the symmetry the structure can be identified as an FCC-like structure with the [100] projections (Fig. 9.8.a,e) and [110] (Fig 9.8.c) seen over 90° of rotation.…”
Section: Effect Of An External Magnetic Fieldmentioning
confidence: 99%